-6(a-3)-7(5-4a)=

Simple and best practice solution for -6(a-3)-7(5-4a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(a-3)-7(5-4a)= equation:


Simplifying
-6(a + -3) + -7(5 + -4a) = 0

Reorder the terms:
-6(-3 + a) + -7(5 + -4a) = 0
(-3 * -6 + a * -6) + -7(5 + -4a) = 0
(18 + -6a) + -7(5 + -4a) = 0
18 + -6a + (5 * -7 + -4a * -7) = 0
18 + -6a + (-35 + 28a) = 0

Reorder the terms:
18 + -35 + -6a + 28a = 0

Combine like terms: 18 + -35 = -17
-17 + -6a + 28a = 0

Combine like terms: -6a + 28a = 22a
-17 + 22a = 0

Solving
-17 + 22a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 17 + 22a = 0 + 17

Combine like terms: -17 + 17 = 0
0 + 22a = 0 + 17
22a = 0 + 17

Combine like terms: 0 + 17 = 17
22a = 17

Divide each side by '22'.
a = 0.7727272727

Simplifying
a = 0.7727272727

See similar equations:

| 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] | | 4-5a=4(1+8a) | | 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 | | X-6-20=142 | | 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 | | I2/3z=9 | | 11-(9x)+2x-(-9)= | | r=d/1-t | | (-t/2)=12 | | 7*z*0=0 | | -11=4a-3 | | -8(1-7n)+7(n+3)= | | 5n-3n+7+2n= | | 24a+72b-40c= | | 13*0*p=0 | | 6j-4j+12=6j-3j+30 | | 42-48v=-54 | | 9=8-x/4 | | 4(2a)-a= | | 4w-5=12w-4 | | (4x^2-1)(6x^2-9)= | | 5(d+5)+2d=-13-8d |

Equations solver categories